The Influence of Entrepreneurial Marketing and Digital Marketing on the Marketing Performance of Property Assets through a Competitive Environment at PT PLN (Persero) Pusdiklat - Fandy Nuary; Adhi Prasetio (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Marketing performance of property asset utilization is influenced by various strategic factors, including entrepreneurial marketing and digital marketing, as well as the competitive environment conditions faced by organizations. This research aims to analyze the influence of Entrepreneurial Marketing and Digital Marketing on the Marketing Performance of property assets through the Competitive Environment at PT PLN (Persero) Pusdiklat, examining both direct and indirect effects via competitive environment conditions. This research used a quantitative approach with a survey method. Data were collected through structured questionnaires distributed to the Implementation Unit, employees, and PIC Beyond kWh within PT PLN (Persero) Pusdiklat. The sample determination technique used the census method with a total of 312 respondents. Data analysis was carried out using PLS-SEM. The results Entrepreneurial Marketing and Digital Marketing have a positive and significant effect on Marketing Performance. Digital Marketing also has a positive and significant effect on the Competitive Environment, while Entrepreneurial Marketing does not significantly affect the Competitive Environment. The Competitive Environment does not have a significant effect on Marketing Performance. Mediation testing shows that the Competitive Environment fails to mediate the relationship between Entrepreneurial Marketing and Marketing Performance, as well as between Digital Marketing and Marketing Performance. The improvement in marketing performance of property asset utilization at PT PLN (Persero) Pusdiklat is more directly influenced by the implementation of Entrepreneurial Marketing and Digital Marketing than through competitive environmental conditions.